Interior Design and Furniture in Traditional Dwellings in the Old Towns between Modernity and Preservation of Cultural Heritage (a Special Case in the Old City of Hebron) - Wisam Shaded; Rawan Jobran (ARCHive-SR, 2023)
This paper discusses the repercussions, challenges, and conditions imposed by the living occupancy in traditional dwellings with the signature spatial organization in the old cities in general and in the Old City of Hebron/Palestine in particular. moreover, this paper examines the interior design of these dwellings in terms of floors, wooden furniture fixed or movable, facilities such as bathrooms and kitchens, the distribution of furniture and its shape and design, furthermore, illustrate the problem that is caused by living in traditional dwellings built in ancient time, containing patterns of spatial designs that were of use in the past but no longer suit the current needs of the inhabitants and modernity. many building foundations in this paper go back to the Mamluk period, However, the rest of them goes back to the Ottoman period. This paper aims to study the possibility of adapting the characteristics and components of traditional dwellings and formulate new models and solutions that enable the inhabitants of these dwellings to live in them while providing comfort and well-being without having to resort to the destruction and total removal of the internal components or replacing them with the modern style, which may not suit the aesthetics and structural feature. in addition, maintain its heritage value, by applying several measures that ensure the best results, within an objective analytical methodology including identifying a few selected models of traditional dwellings, conducting a study, and inheriting it, to reach results advancing the preservation of the cultural heritage and achieving sustainability.